1998
DOI: 10.1016/s1072-7515(98)00207-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hilar Cholangiocarcinoma (Klatskin Tumors) with Hepatic Resection or Transplantation

Abstract: Background-Because of the rarity of hilar cholangiocarcinoma, its prognostic risk factors have not been sufficiently analyzed. This retrospective study was undertaken to evaluate various pathologic risk factors which influenced survival after curative hepatic resection or transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
137
0
13

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(152 citation statements)
references
References 21 publications
2
137
0
13
Order By: Relevance
“…10,[46][47][48][49] Studies assessing the impact of positive surgical margins on outcomes after LT for CCC indirectly support our observations in that outcomes are uniformly poor for patients with CCC undergoing LT with positive resection margins. 22,23 Obtaining disease-free surgical margins appears to be of paramount importance when evaluating potential candidates for LT. However, the use of extended resections in immunosuppressed patients can be associated with significant complication rates, as seen in this series.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,[46][47][48][49] Studies assessing the impact of positive surgical margins on outcomes after LT for CCC indirectly support our observations in that outcomes are uniformly poor for patients with CCC undergoing LT with positive resection margins. 22,23 Obtaining disease-free surgical margins appears to be of paramount importance when evaluating potential candidates for LT. However, the use of extended resections in immunosuppressed patients can be associated with significant complication rates, as seen in this series.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have applied more radical resections and cluster transplantation to patients with extensive CCC undergoing LT. 23,50,51 Outcomes are not good; therefore, patients with CCC extending into other organs probably should not be offered LT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Survival rates of 74% at 1 year, 34% at 3 years, and 9% at 5 years were reported in another series of 34 patients treated by resection. 9 The patients with the most favorable outcome were pathological tumor, node, and metastases stage 0 to 1, with tumor-free surgical margins and disease-free lymph nodes. A recent Japanese series described a remarkable resectability rate of 79% by incorporating partial hepatectomy into 86% of the resection procedures, yielding a 5-year survival rate of 26%.…”
Section: Treatmentmentioning
confidence: 99%
“…A recent Japanese series described a remarkable resectability rate of 79% by incorporating partial hepatectomy into 86% of the resection procedures, yielding a 5-year survival rate of 26%. 9 These investigators suggested that it was particularly important to include resection of the caudate lobe because this is commonly a site of early tumor dissemination.…”
Section: Treatmentmentioning
confidence: 99%